Combined effects of caffeine and aerobic exercise on leptin levels and some indices of insulin resistance in diabetics - Akram Amaghani; Bahram Jamali Gharakhanlou; Ali Zarghami Khamneh; Nima Radkhah (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
The study aimed to examine the combined effects of caffeine and aerobic exercise on leptin levels and some indices of insulin resistance in diabetics Thirty-two males with type 2 diabetes participated in a quasi-experimental and double-blind design. All participants were divided into four homogeneous groups of 8 individuals, including placebo (P), caffeine supplementation (C), aerobic training (AT), and aerobic training and caffeine (AT + C). The design protocol included eight weeks of aerobic exercise and caffeine consumption. Blood samples were taken to measure serum levels of leptin, glucose, insulin, HbA1c, HOMA-IR, and insulin sensitivity (QUICKI) indices at two phases. Data were analyzed by repeated measure ANOVA, Bonferroni posthoc, and independent T-test at a significant level of a s 0.05. The results showed that the levels of leptin, glucose, insulin, HbA1c, and HOMA-IR in the three intervention groups significantly decreased compared to the placebo group (P = 0.001). In addition, QUICKI was significantly increased in the three groups of caffeine (C), aerobic training (AT), and aerobic training + caffeine (AT + C) compared to the placebo group (P = 0.001). Also, the AT+C group has double effects on the investigated indices compared to the caffeine (C) group (P = 0.001). Regular aerobic exercise and caffeine supplementation may be more effective treatments for improving insulin resistance indicators associated with type 2 diabetes.